2011
DOI: 10.1016/j.antiviral.2011.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Oseltamivir-resistant pandemic A(H1N1) 2009 influenza viruses detected through enhanced surveillance in the Netherlands, 2009–2010

Abstract: Enhanced surveillance of infections due to the pandemic A(H1N1) influenza virus, which included monitoring for antiviral resistance, was carried out in the Netherlands from late April 2009 through late May 2010. More than 1100 instances of infection with the pandemic A(H1N1) influenza virus from 2009 and 2010 [A(H1N1) 2009] distributed across this period were analyzed. Of these, 19 cases of oseltamivir-resistant virus harboring the H275Y mutation in the neuraminidase (NA) were detected. The mean 50% inhibitory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…11 The influenza viruses in this background dataset are referred to in the text as 'community influenza viruses'.…”
Section: Cases From National Surveillancementioning
confidence: 99%
“…11 The influenza viruses in this background dataset are referred to in the text as 'community influenza viruses'.…”
Section: Cases From National Surveillancementioning
confidence: 99%
“…While an increased usage of NA inhibitors was expected during the pandemic period, the detection rate of the H275Y NA mutation among A(H1N1)pdm09 viruses was reported as only Ͻ2% in the general population (6,7,46,68). A case-controlled study identified immunosuppression as the major risk factor associated with detection of an oseltamivirresistant H275Y variant among hospitalized patients (6).…”
mentioning
confidence: 99%
“…In 2009, the swine flu pandemic strain of H1N1 (HI1NI pdm09) essentially replaced the circulating oseltamivir-resistant H1N1 viruses. This emergent virus strain is sensitive to oseltamivir, but with its use, resistance continues to develop [30,31].…”
mentioning
confidence: 99%